Yield of Dimethyl Ether and Gasoline as a Function of Morphology of the ZSM-5 Catalyst - Stante, Matteo (2011)
In this project, the catalytic behavior of some zeolite ZSM-5 crystals was evaluated. These crystals were both commercial and prepared at Luleå University of Technology. Catalytic tests done at 250°C and 370°C. Among the tested crystals there were big coffin shaped single crystals and also agglomerates of small grains with the same Si/Al ratio so it should have been possible to evaluate the influence of the morphology on the catalytic activity and the selectivity. The catalysts were characterized using gas adsorption and scanning electron microscopy. For all the catalysts, at the higher temperature, methanol was mostly converted to gasoline and almost no DME was produced because the reaction arrived to completion. It was expected that the more mesoporous crystals should give higher yield of DME at the lower temperature but this was not observed experimentally. This may be caused by that the separation of DME and methanol was not sufficient on the GC column. Validerat; 20110903 (anonymous)